Effect of Robusta Coffee to Multiple Organ Histopathological Change on Rats Strain Wistar - Y. Lestari, Dian; Aleq Sander, M.; Nelasari, Halida; P. Ilahika, Anung; Rahmat, Saidah; Sophia, Meta; Rahman, Deby (International Journal of Engineering and Technology, 2019)
Coffee beans as beverages that contains acrylamide that formed in roasted process. Acrylamide can make multiple organ dysfunction on rats. The atudy aims to prove the effect of Robusta on Morphological changes of Hepatocytes, colonic mucosa, and prostatic acinar on Male rats . True experimental post test only control group design. 24 samples of male rats clustered in 5 groups; control group and treatment group were given steeping doses of coffee (0.36ml, 0.72ml, 1.44ml, and 2.16ml). Analysis of the data using One-Way ANOVA showed that there are significant value 0.000. Steeping of robusta coffee (Coffea canephora var. Robusta) could cause morphological changes of hepatocytes cell, colonic mucosa, and prostatic acinar in male rats (Rattus novergicus Strain Wistar).Â Â